Associations between Government Regulation of Alcohol Availability, Alcohol Use and Health in Australia - Gilmore, William Thomas (Curtin University, 2022)
This PhD program focused on using novel approaches to address gaps in scientific research on health effects of alcohol availability. Two studies on bar trading hours and mental health capitalised on special permits available to Perth bars allowing a proportion to trade past standard closing time. One study on alcohol taxation and sexual health capitalised on a federal tax increase on ready-to-drink alcoholic beverages. The work will contribute to informing evidence-based alcohol policy debate.